2011
DOI: 10.1016/j.cellimm.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-induced suppression of tumor antigen-specific T cell expansion is comparable to suppression of global T cell expansion

Abstract: We have observed that in vivo interaction between melanoma and resting T cells promotes suppression of antigen-driven proliferative T cell expansion. We hypothesized that this suppression would affect tumor antigen-specific T cell populations more potently than tumor-unrelated T cell populations. A B16F10 cell line was stably transfected to express low levels of the lymphocytic choriomeningitis virus (LCMV) glycoprotein GP33 (B16GP33). Mice bearing B16F10 or B16GP33 tumors were infected with LCMV, and prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Importantly, this model employed aggressive in vitro stimulation of effector and memory T cell populations prior to adoptive transfer; consequently, it is possible that this preparative regimen effectively enriched homogenous populations of acutely activated effector T cells in both experimental groups, diluting any potential therapeutic benefit that memory T cells may inherently offer. We previously described the selection of B16F10 melanoma cell line clones stably transfected to express very low and poorly immunogenic levels of the LCMV epitope peptide GP33 (B16GP33) [19]. By rendering GP33 a novel tumor antigen and harvesting effector or memory phenotype GP33-specific CD8+ T cells from mice 8 or >30 days after LCMV infection, respectively, our model enables us to precisely control the phenotype of adoptively transferred tumor antigen-specific T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this model employed aggressive in vitro stimulation of effector and memory T cell populations prior to adoptive transfer; consequently, it is possible that this preparative regimen effectively enriched homogenous populations of acutely activated effector T cells in both experimental groups, diluting any potential therapeutic benefit that memory T cells may inherently offer. We previously described the selection of B16F10 melanoma cell line clones stably transfected to express very low and poorly immunogenic levels of the LCMV epitope peptide GP33 (B16GP33) [19]. By rendering GP33 a novel tumor antigen and harvesting effector or memory phenotype GP33-specific CD8+ T cells from mice 8 or >30 days after LCMV infection, respectively, our model enables us to precisely control the phenotype of adoptively transferred tumor antigen-specific T cells.…”
Section: Discussionmentioning
confidence: 99%
“…To test LCMV-specific memory T cell responses, LCMV-immune mice were infected with 10 6 PFU clone 13 strain LCMV by intravenous injection. Mice were also inoculated with 10 6 B16GP33 cells, previously generated in our laboratory by stable transfecting B16F10 cells to express low levels of the LCMV epitope peptide GP33 [19]. …”
Section: Methodsmentioning
confidence: 99%
“…The B16GP33 cell line was prepared as previously described (10,11). Briefly, B16F10 cells were transfected with a plasmid containing genes for the class I MHC-restricted LCMV surface glycoprotein GP33 and G418 resistance, and the resulting stably transfected cell line was selected by G418 resistance.…”
Section: Methodsmentioning
confidence: 99%
“…This effect appears to be mediated by increased susceptibility of activated T cells to apoptotic cell death [18]. The magnitude of this suppression is proportional to the extent of tumor burden; moreover, this influence is exerted in a globally non-specific manner that affects tumor antigen-specific T cells to the same degree as non-tumor antigen-specific T cells [19]. These observations indicate that the presence of cancer fundamentally alters the homeostasis of newly activated T cells; indeed, we have found that the ability of mice to generate new MPEC is markedly impaired in the presence of melanoma tumors [18].…”
Section: Introductionmentioning
confidence: 99%